Enhancing Learning: Differentiated Instruction in Elementary Schools - Ferrer, Jorna May; Naanep, Nathaniel (Journal of Interdisciplinary Perspectives, 2025)
As individual needs of the learners vary, they need to tailor their learning to meet their diverse, unique demands. This study determined the effectiveness of differentiated instruction techniques in enhancing pupils' learning outcomes to selected elementary schools in Tampakan, South Cotabato, for 2024- 2025 academic year using a quantitative research design, which is descriptive and correlational, respondents included selected grades 4 to 6 pupils and all teachers from ten schools, using stratified random sampling for pupils. Statistical tools such as mean scores and Pearson’s r correlation were used to analyze the data. Findings showed that differentiated instruction techniques, including hands-on exploration, varied instructional materials, visual aids, graphic organizers, and scaffolded tasks, were highly implemented. The pupils responded highly to differentiated instruction in motivation and engagement, with a section mean of 4.63. Additionally, the academic achievement of the respondents obtained a mean of 85.55, Science with the highest mean of 85.94, and Mathematics the lowest at 85.34. A moderate, positive correlation was determined between the implementation of differentiated instruction and pupils' motivation, engagement, and performance in academic areas. Identified challenges included time constraints, resource limitations, and classroom management, highlighting the need for strategic support. The study concluded that differentiated instruction enhances inclusive learning but requires robust support mechanisms.